The use of different models of physical exercises performed at home during the COVID-19 pandemic: positive and negative points - Miguel, H.; de Almeida Campos, M. V. (International Journal of Medicine and Health, 2020)
In this way, we seek to address quickly and concisely, the positive and negative points of the main models of physical training performed during this quarantine period. It is important to note that before carrying out any physical activity, the relationship between the cost x benefit of it needs to be a highlight. In addition, we must avoid osteoarticular damage, as well as maximizing the effectiveness of the chosen model will be essential for more effective training that generates adequate benefits for the performer.